231 NURSING HOME RESIDENTS PRESENTING TO THE EMERGENCY DEPARTMENT WITH FALLS. (25th October 2022) - O'Connor, A; Fallon, A; Noonan, C; McElwaine, P; Kennelly, S
Abstract: Background: Nursing Home Residents (NHR) are the most-frail group of older persons, with many comorbidities that increase their risk of falling. Falls are a frequent reason for ED attendance by NHR's as it is for all older persons, but little is reported on their characteristics and outcomes specifically. Methods: A prospective cohort study of all NH presentations with falls to the ED of a university teaching hospital over a one-year period. Detailed operational and clinical phenotype characteristics, and outcomes were recorded in all instances. Results: There were 519 ED presentations by 344 NHR over one year. Almost half of all presentations (48.2%, 250/519), were as result of a fall, by 172 residents. The majority were female (137/250, 55%), with an average age of 77.8 years (±10.8). Many, 84.3% (145/172), had a prior fall in the past six-months. Almost half had a diagnosis of dementia (124/250, 49.6%). A third mobilised with a Zimmer-frame (83/250), and 10.8% (27/250) wheelchair. 33.2% (83/250) had visual impairment. The mean Barthel Index was 9.55 (±5.12) indicating high-dependency. NHRs fallers frequently attended ED outside routine working hours, with 36.8% (92/250) and 27.6% (69/250) presenting after 5pm (Monday to Friday), or at the weekend respectively. 54.8% of patients were admitted (137/250), and only 25.6% of patients had review by a GP prior to ED-referral (64/250). The average Length Of Stay (aLOS) for admitted NHR fallers was 10.4 (±9.1) days. Injurious falls were noted in only 10.4% (26/250) presentations. aLOS for those admitted with documented injuries (14/26, 54%) was 5.0 days (±7.0, n=14). Conclusion: NH residents have complex clinical needs and falls is a frequent reason for attending ED. Better access to "out of hours" clinical support within the NH, and better integrated falls prevention programmes/ care pathways between NHs and primary/secondary services are necessary to enhance care and optimise falls prevention.